2010
DOI: 10.1093/ejo/cjq166
|View full text |Cite
|
Sign up to set email alerts
|

Resonance frequency analysis of orthodontic miniscrews subjected to light-emitting diode photobiomodulation therapy

Abstract: The aim of this prospective experimental study was to evaluate the effect of light-emitting diode (LED) photobiomodulation therapy (LPT) on the stability of immediately loaded miniscrews under different force levels, as assessed by resonance frequency analysis (RFA). Sixty titanium orthodontic miniscrews with a length of 8 mm and a diameter of 1.4 mm were implanted into cortical bone by closed flap technique in each proximal tibia of 15 New Zealand white adult male rabbits (n = 30). The animals were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 26 publications
1
26
1
7
Order By: Relevance
“…A pilot study was performed just before the experimental stage of this research, in which the mini screws were placed in the tibia of the rabbits; [24][25][26] however, unfortunately it was detected that the legs of the animals were broken because of the weak bone structure. It was thought that length of the mini screw could be the cause of the fracture, but as the most commonly used length of the mini screws is 8 mm in orthodontic practice, it was decided to change the experimental bone to the fibula, rather than changing the dimension of the mini screw.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study was performed just before the experimental stage of this research, in which the mini screws were placed in the tibia of the rabbits; [24][25][26] however, unfortunately it was detected that the legs of the animals were broken because of the weak bone structure. It was thought that length of the mini screw could be the cause of the fracture, but as the most commonly used length of the mini screws is 8 mm in orthodontic practice, it was decided to change the experimental bone to the fibula, rather than changing the dimension of the mini screw.…”
Section: Discussionmentioning
confidence: 99%
“…This can be useful for stability measurement in animal studies if it is made accurately, but for clinical use this would prevent attaching any kind of mechanics for tooth movement. 28 The mini-implants used in this study have an industrially fabricated inner thread at the top. It is made for fixation of prefabricated abutments to create different kind of mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…44 In another study by OsseoPulse ® LED device, a favorable effect on healing and stability of 12 titanium orthodontic miniscrews was reported. 45 The results of our study and those of others indicated that bone irradiated with LED arrays showed increased neovascularization, collagen deposition, and bone neorformation compared to non-irradiated bone. In addition to these studies, our results have demonstrated that the use of BioOss ® is effective in the healing of bone defects and that combining it with LPT improves the outcomes of this therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%